Investigation and utilization of lactic acid bacteria for cider maturation processes. - Daosheng Zhang (2004)
Investigation and utilization of Lactic Acid Bacteria for cider maturation processes Cider maturation involves a number of transformations mediated by Lactic Acid Bacteria (LAB). A comparison of two heterofermentative lactic acid bacteria (Oenococcus oeni 11648 and Lactobacillus brevis X2), capable of malolactic fermentation, was made to assess the relative merits of these two organisms in cider maturation processes. Initial work studied LAB propagation on safe (free of animal extracts) simple media. Optimum growth conditions were determined. The two strains were shown to be highly adapted to the cider environment being able to tolerate ethanol, up to 10% (v/v). O. oeni was shown to be more tolerant to ethanol and low pH condition compared to L. brevis. The growth of both strains was significantly stimulated by low levels of glucose (~ 1mM) in the presence of organic acids (5g/l malate) such that the specific growth rate and cell yield were stimulated by 167% and 260% respectively. The growth of the organisms was studied in batch, continuous and membrane bioreactor (MBR) systems with pH control. The highest maximum specific growth rates of O. oeni with 0.066h-1 was obtained at pH 4.5 when the mixture of 5g/l glucose-5g/l fructose was added to the culture medium, while L. brevis with 0.110h-1 was obtained at pH 5.5 in the 10g/1 glucose medium. Both strains were grown in continuous cultures at a variety of dilution rates and the precise growth parameters were determined and these data show that L. brevis gave higher biomass yield (Yx/smax), faster volumetric cell productivity (Qxmax) higher ATP yield (YATPmax) than O. oeni. In the MBR culture system, the growth of two LAB showed that high cell concentrations were possible, O. oeni cultures to 12 g/1 of dry weight, this is over 32 times higher than batch (0.357 g/1) and continuous culture (0.37 g/1). The volumetric productivities of the three systems were 7.9 mg/l/h, 17.6 mg/l/h and 180mg/l/h in batch, continuous culture and MBR respectively. Similar results were obtained for the growth of L. brevis. Having produced high cell concentrations of O. oeni and L. brevis in the MBR, the system was employed for rapid, continuous malolactic transformation of synthetic green cider medium. The levels of malate removed were a function of the residence time and the alcohol concentration. Starting with 2 g/1 malate, over 85% could be removed using a 6 hour residence time and compared very favourably with conventional batch fermentations that take typically 20 - 40 days. The MBR system was run successfully for a period of over 9 days and with correct management could be run for much longer periods. In these conditions, O. oeni showed greater stability and viability than L. brevis in cider environment as it is more alcohol and acid tolerant. These studies provide a basis for developing strategies for rapid maturation of cider using an MBR system. Future work for further optimization of the MBR operation with real cider is discussed. The economic viability of MBR in cider maturation needs to be assessed.